1967
DOI: 10.1021/ja01002a063
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysis of exo- and endo-5-methoxy-2,3-diazabicyclo[2.2.1]-2-heptene

Abstract: The Rh is octahedrally coordinated. Four positions are taken up by the porphyrin pyrrole nitrogen atoms (Rh-N average distance 2.04 A); a chloride ion (Rh-Cl distance of 2.35 A) and a phenyl group that is -bonded to the Rh (Rh-C distance 2.05 A); complete the coordination. The phenyl group is approximately perpendicular to the mean porphyrin plane.The mechanism of formation and chemistry of this interesting species is presently under investigation.23 (23) This research was supported by grants from the Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

1969
1969
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 0 publications
2
27
1
Order By: Relevance
“…First, experiments showed that N 2 loss results in bicyclo products 3 and 4 with a nonstatistical preference for the exo product in a 4.7:1 ± 0.9 (exo:endo) ratio. , The statistical ratio would be 1:1 if the intervening 1,3-singlet diradical intermediate 2 were to undergo complete IVR prior to C–C bond formation. Second, several qualitative theories for the origin of selectivity have been proposed, beginning with Roth and Martin, , Allred and Smith, and culminating with Carpenter’s in-depth description that the nonstatistical exo:endo ratio results from a relatively low barrier (∼2 kcal/mol) for transition-state TS2 ( endo-TS2 and exo-TS2 , see Scheme ), which results in C–C bond formation without IVR. , More specifically, Carpenter’s description focused on the out-of-plane bending motion of the methylene (CH 2 ) bridge group that leads to the unexpected excess of exo product 3 , and this rationale was qualitatively supported by classical trajectory analyses and experiments in supercritical propane . Third, density functional theory (DFT) quasiclassical trajectories have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…First, experiments showed that N 2 loss results in bicyclo products 3 and 4 with a nonstatistical preference for the exo product in a 4.7:1 ± 0.9 (exo:endo) ratio. , The statistical ratio would be 1:1 if the intervening 1,3-singlet diradical intermediate 2 were to undergo complete IVR prior to C–C bond formation. Second, several qualitative theories for the origin of selectivity have been proposed, beginning with Roth and Martin, , Allred and Smith, and culminating with Carpenter’s in-depth description that the nonstatistical exo:endo ratio results from a relatively low barrier (∼2 kcal/mol) for transition-state TS2 ( endo-TS2 and exo-TS2 , see Scheme ), which results in C–C bond formation without IVR. , More specifically, Carpenter’s description focused on the out-of-plane bending motion of the methylene (CH 2 ) bridge group that leads to the unexpected excess of exo product 3 , and this rationale was qualitatively supported by classical trajectory analyses and experiments in supercritical propane . Third, density functional theory (DFT) quasiclassical trajectories have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1965, mechanistic studies have revealed that the structures of short-lived and elusive diradicals were essential to understand the selective formation of inversion product inv- CP . Computational studies at the CASPT2//CASSCF level of theory predict that 1,3-diradicals DR and 1,5-diazenyl diradicals DZ are responsible for the selectivity between the product with retained stereochemistry, ret- CP , and its inverted counterpart, inv- CP (Scheme ). Homolytic substitution (S H 2) involving the equatorial diazenyl diradical, eq- DZ , offers a plausible pathway for the formation of inv- CP . , The Closs-type planar singlet diradical intermediate, pl- DR , , is common to both ret- CP and inv- CP .…”
Section: Introductionmentioning
confidence: 99%
“…6 Rate constant for decay of sensitizer triplet (see Herkstroeter and Hammond in footnote a). 6 Intersystem crossing efficiency. d Uncorrected for direct photolysis.…”
Section: Resultsmentioning
confidence: 99%
“…d Uncorrected for direct photolysis. 6 Value in ethanol: C. A. Parker and T. A. Joyce, Trans. Faraday Soc., 62, 2785 (1966).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation